TRANSFORMASI NILAI PENDIDIKAN AGAMA HINDU DALAM BUDAYA MEDIA SOSIAL PADA GENERASI MUDA HINDU BALI - I Gede Made Boga Asta Wiguna (Yayasan Pendidikan Literasi Borneo, 2026)
This study aims to analyze the transformation of Hindu religious education values within social media culture among Balinese Hindu youth. The development of social media has influenced how young people understand, practice, and express Hindu religious values in the digital era. This research employed a qualitative approach with a descriptive-interpretative design. Data were collected through observation, interviews, documentation, and literature study. The findings show that social media has become a new space for Hindu religious education among Balinese Hindu youth. The values of tattwa, susila, and acara have changed in form and delivery according to the visual and interactive nature of digital culture. Social media provides opportunities to spread Hindu teachings in more creative and accessible ways. However, it also creates challenges such as superficial spiritual understanding, performative religiosity, and commodification of religious symbols. This study suggests that Hindu religious education needs adaptive and contextual approaches to remain relevant in the digital culture of the younger generation.